Investigation of the weed vegetation at the Varga Organic Farm in Püspökhatvan - Pál, János (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
Investigation of the weed vegetation was carried out on three fields of the Varga Organic Farm (Püspökhatvan, Hungary) in six different crops (winter wheat, rye, oat, corn, pea and oil pumpkin) in 2002 and 2003. In altogether 650 1 1 meter quadrats the list of weed species was compiled and the abundance of each species was estimated. The total number of weed species found on the different fields was between 16 and 29. Altogether 76 species were detected on the investigated fields of the farm. The total abundance of the weeds varied between 0,5% in the rye and 55% in the winter wheat. The large difference between the abundances of the weed vegetations in the different years was probably caused by the extreme weather conditions in 2003. The dominant weed species of the investigated crops were Artemisia vulgaris, Cirsium arvense, Chenopodium album, Convolvulus arvensis, Ambrosia artemisiifolia and Elymus repens. It can be concluded that most abundant on the investigated fields of the organic farm are perennial species (hemicryptophytes and geophytes).
Keywords: organic farm; ecological farm; weeds; weed control